Use of GIS to analyse the impacts of controlling trypanosomosis - Okello, O.O.; Kruska, Russell L.; Reid, Robin S. (OAU/STRC, 1999)
Better data: currently, the quality of GIS analyses is constrained by poor data on the distribution of current tsetse populations, non-human and human trypanosomosis prevalence, livestock population densities, agricultural production, biodiversity, soil fertility, land-use, infrastructure, income, markets, etc. More and better analysis: most of the current focus is on the production of maps, with little use of powerful GIS analysis tools. Better use needs to be made of exploratory analysis techniques, statistical analyses, spatial data analysis. Integration with other modelling tools: To date, GIS software does not incorporate tools to model system dynamics. GIS tools need to be better linked with other analysis tools to improve our understanding of system change after tsetse control.